2000
DOI: 10.1515/hf.2000.003
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Nature of Kiln Brown Stain in Radiata Pine

Abstract: This paper presents results of a study on the chemical nature of kiln brown stain (KBS) that develops in kiln dried radiata pine (Pinus radiata D. Don) sapwood. KBS is a chocolate brown discolouration which develops approximately 0.5 mm under the timber surface. Stain free radiata pine was achieved during drying trials on "green" radiata pine sapwood which had been treated to extensive cold and hot water extraction. Differences in chemical composition between the sap and hot water extract were observed. Chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
1
36
0
1
Order By: Relevance
“…During drying, for some species (mainly softwoods), hydrophilic and lipophilic extractives migrate towards the surface and become distributed on the board surface causing a brown stain. Zavarin (1984), Lavisci et al (1991), Terziev (1995, Wiberg (1996), Schmidt and Kreber (1998), Terziev and Boutelje (1998), Terziev and Nilsson (1999), McDonald et al (2000) suggested the formation of kiln brown stain in radiata pine. P. radiata is associated with elevated contents of reduced sugars and amino acids.…”
Section: Causes Of Wood Discoloration 41 Heatmentioning
confidence: 98%
See 1 more Smart Citation
“…During drying, for some species (mainly softwoods), hydrophilic and lipophilic extractives migrate towards the surface and become distributed on the board surface causing a brown stain. Zavarin (1984), Lavisci et al (1991), Terziev (1995, Wiberg (1996), Schmidt and Kreber (1998), Terziev and Boutelje (1998), Terziev and Nilsson (1999), McDonald et al (2000) suggested the formation of kiln brown stain in radiata pine. P. radiata is associated with elevated contents of reduced sugars and amino acids.…”
Section: Causes Of Wood Discoloration 41 Heatmentioning
confidence: 98%
“…Biochemical reactions are mentioned by Kreber et al (1998) and McDonald et al (2000), suggesting that the formation of kiln brown stain in radiata pine, P. radiata, is associated with elevated contents of reducing sugars and amino acids, which form MaillardAmadori type compounds at elevated temperatures. Decomposition of polyoses yields elevated amounts of soluble carbohydrates.…”
Section: Biochemical Reactionsmentioning
confidence: 99%
“…Their study proposed that E* occurred during heat treatment results from chemical changes in lignin due to the darkening of the lignin which was associated with the generation of chromophoric groups, mainly the increase in carbonyl groups. McDonald et al (2000) stated that when wood was exposed to high temperatures, aldehydes and phenols were formed, which led to the formation of colored compounds as a result of the chemical reactions that occurred.…”
Section: Color Changesmentioning
confidence: 99%
“…Amino acid composition (free and bound) was performed according to the method described by McDonald et al [29]. Briefly, protein in the RBB (20 mg) was hydrolyzed in hydrochloric acid into amino acids, and then free/hydrolyzed amino acids were sequentially derivatized using acetylchloride/isobutanol (1:4 v/v) mixture followed by heptafluorobutylanhydride in CH 2 Cl 2 .…”
Section: Chemical Compositionmentioning
confidence: 99%